Study of Ethnopharmaceutical Plants with Anti-Inflammatory Properties In Loa Lepu Village, Kutai Kartanegara - Siti Sulayha; Paula Mariana Kustiawan (Jurnal Serambi Engineering, 2022)
Medicinal plants is mostly used by tribes in Indonesia, one of them is the Loa Lepu Village community. Excavation of information on the use of medicinal plants can be done by using the ethnopharmaceutical method. This study was conducted to determine the use of plants as anti-inflammatory drugs, how to make them, how to use plants as anti-inflammatory drugs in Loa Lepu Village. Determination of informants in the Loa Lepu Village Community using the Snowball method and purposive sampling of 15 informants, followed by semi-structured interviews. The results obtained 15 types of medicinal plants used for anti-inflammatory by the people of Loa Lepu village which were divided into 10 families. The most widely used plant family was the Zingiberaceae family with 5 plants, namely ginger (Zingiber officinale Roscoe), laos (Alpinia galangal L. Willd), kencur (Kaempferia galangal L.), temulawak (Curcuma xanthorriza) and turmeric (Curcuma domestica). The most widely used plant parts are the leaves and rhizomes, then the method of use that is most often done is boiled